The Effects of Poverty on Rural Lively Hoods: A Case Study of Bufumbo Sub-County and Bufumeo Sub-Couny, Mbale District. - Muduwa, Jennifer (Kabale University, 2023)
Uganda has made progress towards poverty elimination in rural areas having successfully achieved the Millennium Development goal target of halving the number of people in extreme poverty way ahead of the 2015 deadline. Uganda is on course to achieve its national target of reducing this number to 10% by 2017. Despite this progress, significant inequality still exists and in regions like Bufumbo sub-county, Mbale district over 25% of people are still living in extreme poverty. This is because progress in reducing poverty has been very slow in Eastern parts of Uganda. The major objective of the study was to investigate the effects of poverty on rural lively hoods in Bufumbo sub-county, Mbale district